The Intellectual Capital Effect on Financial Performances at Islamic Insurance - Rizqon Halal Syah Aji; Kurniasih Kurniasih (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
The research has analyzed the intellectual capital effect of the Islamic insurance company’s financial performance. Intellectual capital is quantified by VAICTM (Value Added Intellectual Capital), for efficiency components are physical capital coefficient (VACA), human capital coefficient (VAHU), and structural capital coefficient (STVA). Financial performance is quantified by ROA and RBC. Data is given from seven Islamic insurance companies during 2009-2013. Data analysis used is PLS (Partial Least Square). The result shows that intellectual capital factors had an affect the company’s financial performance. Intellectual capital relation to financial performance parameter value estimated coefficient 0,845 with t-statistic 46,771. VAICTM enables to elucidate financial performance variable 71, 6%, is by finding the R-square PERF value (financial performance) 0,716.DOI: 10.15408/aiq.v7i2.1696